G protein‐biased kratom‐alkaloids and synthetic carfentanil‐amide opioids as potential treatments for alcohol use disorder. (24th January 2020) - Gutridge, Anna M.; Robins, Meridith T.; Cassell, Robert J.; Uprety, Rajendra; Mores, Kendall L.; Ko, Mee Jung; Pasternak, Gavril W.; Majumdar, Susruta; van Rijn, Richard M.
Abstract : Background and Purpose: Mitragyna speciosa, more commonly known as kratom, is a plant that contains opioidergic alkaloids but is unregulated in most countries. Kratom is used in the self‐medication of chronic pain and to reduce illicit and prescription opioid dependence. Kratom may be less dangerous than typical opioids because of the stronger preference of kratom alkaloids to induce receptor interaction with G proteins over β‐arrestin proteins. We hypothesized that kratom (alkaloids) can also reduce alcohol intake. Experimental Approach: We pharmacologically characterized kratom extracts, kratom alkaloids (mitragynine, 7‐hydroxymitragynine, paynantheine, and speciogynine) and synthetic carfentanil‐amide opioids for their ability to interact with G proteins and β‐arrestin at μ, δ, and κ opioid receptors in vitro. We used C57BL/6 mice to assess to which degree these opioids could reduce alcohol intake and whether they had rewarding properties. Key Results: Kratom alkaloids were strongly G protein‐biased at all three opioid receptors and reduced alcohol intake, but kratom and 7‐hydroxymitragynine were rewarding. Several results indicated a key role for δ opioid receptors, including that the synthetic carfentanil‐amide opioid MP102—a G protein‐biased agonist with modest selectivity for δ opioid receptors—reduced alcohol intake, whereas the G protein‐biased μ opioid agonist TRV130 did not. Conclusion and Implications: Our results suggest that kratom extracts can decrease alcohol intake but still carry significant risk upon prolonged use. Development of more δ opioid‐selective synthetic opioids may provide a safer option than kratom to treat alcohol use disorder with fewer side effects. Abstract : ▪